Unveiling the genetic potential of Terminalia chebula Retz. accessions from North-East and South India: A morphometric analysis - Shobith Murthy Mahadeva; Umesh Kanna Subramani; Parthiban Kalappan Thangamuthu; Devanand Pachanoor Subbian; Radha Palaniswamy; Senthilraja Kandasamy; Venkatesan Subramanian (Trees, Forests and People)
This study examined genetic diversity and growth performance of thirty Terminalia chebula genotypes from various regions of India. Seedlings were evaluated for growth attributes over 180 days after transplanting (DAT). Significant variations were observed across accessions for traits like shoot length, root length, collar diameter and volume. MHTC 04 showed superior performance, with maximum shoot length (36.23 cm) and root length (38.47 cm) at 180 DAT. KETC 05 exhibited the highest collar diameter (1.08 cm) and volume index (39.35) at 180 DAT. The genetic analysis revealed low to moderate PCV and GCV for most traits. Volume index showed the highest PCV (47.31 %) and GCV (47.23 %). High heritability (>95 %) was observed for several traits viz., root length, collar diameter and volume index. Path coefficient analysis identified collar diameter and shoot fresh weight as having the strongest positive direct effects on quality index. Cluster analysis grouped 30 genotypes into 10 clusters with cluster II being the largest (8 progenies). Quality index contributed the maximum (59.30 %) towards divergence followed by shoot dry weight (13.94 %) and volume index (8.28 %). This study identified promising genotypes and important traits for T. chebula improvement programmes, highlighting the potential for selective breeding to enhance the seedling quality and growth performance.